Khotbah Dalam Bingkai Eklesiologi Gereja Toraja Dan Teori-Teori Komunikasi - Yan Piter (Departement of Mathematics Education, 2024)
This research focuses on the Toraja Church, which has a distinctive worship pattern and liturgy, to explore how messages in sermons are delivered and received. The importance of this study lies in understanding how the integrity of the preacher and the different types of sermon messages (theological, sociological, moral, ethical and spiritual) influence church life and daily religious practices. This research aims to analyze preaching practices in the Toraja Church through a qualitative approach. The methods used include documentation study, observation, and indirect interviews with church assembly members, pastors, elders, and deacons. The data collected included written documents, observation notes, and interview results which were then transcribed and coded to identify key themes. The results of the analysis show that sermons in the Toraja Church contain theological, moral, sociological, ethical, and spiritual messages, which are influenced by the integrity of the preacher and the liturgical model used. Sermons serve as an important tool in shaping theological understanding and strengthening congregational faith, with significant influence on congregational response. Effective preaching practices in the Toraja Church integrate various messages and liturgical dimensions, which contribute to the spiritual growth of the congregation and the harmony of the church community.